2019
DOI: 10.1016/j.laa.2019.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Halmos' two projections theorem for Hilbert C⁎-module operators and the Friedrichs angle of two closed submodules

Abstract: Halmos' two projections theorem for Hilbert space operators is one of the fundamental results in operator theory. In this paper, we introduce the term of two harmonious projections in the context of adjointable operators on Hilbert C * -modules, extend Halmos' two projections theorem to the case of two harmonious projections. We also give some new characterizations of the closed submodules and their associated projections. As an application, a norm equation associated to a characterization of the Friedrichs an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…To our knowledge, it is an open question whether the intersection of complemented submodules is again complemented. In [LMX,Section 3] it was shown that even in case all the projections exist, (1.1) need not not hold (see Remark 1.2 below).…”
Section: Concordant Submodulesmentioning
confidence: 99%
See 3 more Smart Citations
“…To our knowledge, it is an open question whether the intersection of complemented submodules is again complemented. In [LMX,Section 3] it was shown that even in case all the projections exist, (1.1) need not not hold (see Remark 1.2 below).…”
Section: Concordant Submodulesmentioning
confidence: 99%
“…The pair (M, N ) being concordant is strictly stronger than the requirement that M ∩N be complemented. In [LMX,Section 3] it is shown that for…”
Section: Concordant Submodulesmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown in [4,Theorem 13] that P Q − Q P is Moore-Penrose invertible if and only if both P Q P and P − Q are Moore-Penrose invertible. Later, it was proved in [5,Theorem 11 and Corollary 12] that P Q − Q P is Moore-Penrose invertible if and only if (P Q) k ±(Q P) k are Moore-Penrose invertible for every k ∈ N. An interpretation of the latter characterization was given in [5,Section 3] using Halmos two projections theorem [1,6].…”
Section: Introductionmentioning
confidence: 99%